Electronic and Superconducting Properties of Some FeSe-Based Single Crystals and Films Grown Hydrothermally - Dong, Xiaoli; Zhou, Fang; Zhao, Zhongxian (Frontiers in Physics, 2020)
Our recent year’s studies of the physical properties of the prototypal FeSe and molecule-intercalated (Li,Fe)OHFeSe superconductor systems are briefly reviewed here, with emphasis on the link between the superconducting and normal-state properties observed in the single crystals and films. These samples were successfully synthesized by our recently developed soft-chemical hydrothermal methods, which are also briefly described. Particularly in the Mn-doped high-Tc (Li,Fe)OHFeSe film, a strong enhancement of the superconducting critical current density was achieved, which is promising for practical application of the superconductivity.